2007
DOI: 10.1002/jor.20471
|View full text |Cite
|
Sign up to set email alerts
|

Use of a bioscaffold to improve healing of a patellar tendon defect after graft harvest for ACL reconstruction: A study in rabbits

Abstract: Following harvest of a bone-patellar tendon-bone (BPTB) autograft, the central third of the patellar tendon (PT) does not heal well. The healing tissues also form adhesions to the fat pad and can cause abnormal patellofemoral joint motion. The hypotheses were that a bioscaffold could enhance patellar tendon healing through contact guidance and chemotaxis, and the scaffold could serve as a barrier to decrease adhesion formation between the neo-PT and infrapatellar fat pad. In 20 New Zealand White rabbits, a cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…The urinary bladder matrix (UBM), another ECM bioscaffold that arouses interests in its potential applications, has also been characterized and tested in pre-clinical studies [3,13,14]. In our research center, we have demonstrated that porcine SIS bioscaffolds can improve the morphological, biochemical and biomechanical properties of healing ligaments and tendons in different animal models [15][16][17][18].…”
Section: Introductionmentioning
confidence: 94%
“…The urinary bladder matrix (UBM), another ECM bioscaffold that arouses interests in its potential applications, has also been characterized and tested in pre-clinical studies [3,13,14]. In our research center, we have demonstrated that porcine SIS bioscaffolds can improve the morphological, biochemical and biomechanical properties of healing ligaments and tendons in different animal models [15][16][17][18].…”
Section: Introductionmentioning
confidence: 94%
“…SIS from swine displays very low immunogenicity without provoking immune-mediated inflammatory reactions when transplanted. To date, SIS has been extensively used as scaffolds for tissue engineering applications of artery [7], bladder [8], intestinal tract [9,10], and tendon [11]. The US FDA has approved its use in human for urogenital procedures, such as hernia repair, cystoplasties, ureteral reconstructions, stress incontinence, peyronie's disease, penile chordee, even urethral reconstruction for hypospadias and strictures [12e16].…”
Section: Introductionmentioning
confidence: 99%
“…45,46 Other investigators have evaluated biologic scaffolds, such as small intestinal submucosa, dermis, fascia lata, pericardium, and decellularized tendon or tendon slices for repair of tendon and ligament. 5,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] While these other tissue matrices have shown some ability to induce tendon or ligament formation, the ECM components from native tendon appear to be critical for differentiation because depletion of key ECM components from tendon impairs tendon formation by tendon progenitor cells. 4 Decorin inhibits type I collagen fibrillogenesis during repair, but is critical for normal fibrillogenesis in tendon development when expression increases rapidly and then decreases to a steady state.…”
Section: Introductionmentioning
confidence: 99%